Work-related and Prostate cancer of man and woman in Mosul/Iraq - Aldin, Shaymaa Z. Jalal (International Journal of Psychosocial Rehabilitation, 2020)
Prostate cancer was more common in men over the age of 65 years. There are 15% cases with positive family history of this disease worldwide. Prostate cancer was the second cause of death among the U.S. in men. Prostate cancer incidence was strongly related to age with the highest rates in older man. Globally millions of people were suffering from this disease. The aims of this study are to provide awareness about prostate cancer as well as an updated knowledge about the epidemiology and etiology. Factors which may deals with the in develop of prostate cancer includes smoking, heavy alcohol consumption, daily chemical exposure, radiation, sun exposure, and some viruses and bacteria. However daily exposure to the chemical play a big role in their disease but the mechanism still unknown. Dealing with the carcinogen should be with caution and it doesn't mean getting cancer after period time. It depends on what you were exposed to, how often you were exposed, and how much you were exposed to, among other things. An early link between cancer and a chemical was found in the late 1700s.whenan English physician noted that a large number of chimney sweeps had cancer of the scrotum due to exposure to soot, which contains chemicals known as polycyclic aromatic hydrocarbons. Since then, many more chemicals have been identified as known or suspected causes of cancer. Today, much of what we know about chemicals causing cancer in humans we had learned from workers exposed to chemicals at their jobs.This study was conducted in Mosul city in north of Iraq for healthy people working in the Department of Chemistry and Lifes Sciences of males and females for the period betwean (July 2011-May 2015 )follow up was included in this study with three month interval to make the comparison and to know if there is regresses or not among the three periods with the compare carcogenic with the control group from persons not exposed to chemicals in there. The results of this study showed that there was a significant impact of exposure to chemicals and biological materials on the development and of prostatic cancer through a significant increase of serum tests during follow-up of people working in the field of chemistry and life sciences and symptoms may in some cases death to some people study there were a mortality between these chemical workers in this study.